2023
DOI: 10.1002/macp.202300199
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Polymerization Modifications to Prepare Biomedical Nanocarriers with Varying Internal Structures, their Properties and Impact on Protein Corona Formation

Johannes Kockelmann,
Rudolf Zentel,
Lutz Nuhn

Abstract: The reactive ester approach provides access to various types of drug delivery systems. Either amphiphilic block copolymer micelles with hydrophobic cores can be generated for encapsulation of hydrophobic drugs, or they are (reversibly) crosslinked by polar molecules into nano(hydro)gel particles affording hydrophilic cores and coronas. Beyond short oligonucleotides complexation or covalent drug conjugation inside the core, a surface functionalization with targeting units is further possible to address a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 156 publications
(351 reference statements)
0
2
0
Order By: Relevance
“…Reports have shown that activated ester polymers such as poly­( N -acryloxysuccinimide) (PNAS) and poly­(pentafluorophenyl) acrylate (PPFPA) react fast and quantitively with primary or secondary amines resulting in the corresponding poly­(acrylamide) (P­(AAm)) derivatives. , While among activated ester monomers, NAS is the oldest and the most regularly employed one, , polymers derived from PFPA commonly feature a higher hydrolytic stability and enhanced solubility in a wider range of organic solvents . Previously, PNAS and PPFPA were already employed to synthesize various polymer architectures, such as activated polymer brushes , and nano­(hydro)­gels . The modification of activated ester polymers with cross-linking bis-amines, amino-modified chromophores, , amino-sugars, and alkylated amines has been shown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that activated ester polymers such as poly­( N -acryloxysuccinimide) (PNAS) and poly­(pentafluorophenyl) acrylate (PPFPA) react fast and quantitively with primary or secondary amines resulting in the corresponding poly­(acrylamide) (P­(AAm)) derivatives. , While among activated ester monomers, NAS is the oldest and the most regularly employed one, , polymers derived from PFPA commonly feature a higher hydrolytic stability and enhanced solubility in a wider range of organic solvents . Previously, PNAS and PPFPA were already employed to synthesize various polymer architectures, such as activated polymer brushes , and nano­(hydro)­gels . The modification of activated ester polymers with cross-linking bis-amines, amino-modified chromophores, , amino-sugars, and alkylated amines has been shown.…”
Section: Introductionmentioning
confidence: 99%
“… 34 Previously, PNAS and PPFPA were already employed to synthesize various polymer architectures, such as activated polymer brushes 32 , 37 and nano(hydro)gels. 38 The modification of activated ester polymers with cross-linking bis-amines, 39 amino-modified chromophores, 40 , 41 amino-sugars, 31 and alkylated amines 42 has been shown. They have further been modified with small peptides.…”
Section: Introductionmentioning
confidence: 99%